(untitled) (Malaysian Management Journal, 2023)
Consumption of vitamins can lower the risks of various noncommunicable diseases (NCDs). Nevertheless, only a small proportion of adults in Malaysia consume vitamin supplements, and this may contribute to the increase in the prevalence of NCDs across the country. Despite the high prevalence of NCDs and low consumption of vitamin supplements, there is insufficient research that assess individuals’ use and expenditure on vitamin supplements. The objective of the present study is to examine the effects of sociodemographic factors on vitamin supplement spending among youth in Malaysia. The primary survey data were collected using convenient sampling (n = 482). In addition to one-way analysis of variance (ANOVA), a lognormal hurdle model was used to explore factors affecting consumption and amount decisions of vitamin supplements. Results of the present study showed that higher-income and less-educated individuals spent more on vitamin supplements compared to lower-income and welleducated individuals. Expenditure on vitamin supplements was higher among Chinese than Malays. Being male and married increased the likelihood of consuming vitamin supplements. In conclusion, sociodemographic factors play an important role in determining consumption and expenditure on vitamin supplements. With the present study’s findings, policymakers could better understand which cohorts of the Malaysian population to be focused on. Therefore, a more effective policy directed towards promoting the use of vitamin supplements can be formulated.